2015
DOI: 10.1016/j.jadohealth.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Young Drivers and Their Passengers: A Systematic Review of Epidemiological Studies on Crash Risk

Abstract: A systematic review of the literature was conducted to appraise the evidence from epidemiological studies of crash risk in young drivers accompanied by passengers, compared with solo driving. Databases searched included the Cochrane Library, Embase, Scopus, Transportation Research Information Services, and Web of Science for studies published between January 1, 1989 and August 1, 2013. Epidemiological studies were selected for review if they focused on crashes of young drivers (≤24 years old) and included both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 28 publications
3
49
1
Order By: Relevance
“…Driving with a teenage passenger is considered to be a factor uniquely associated with teen crash risk (Williams et al, 2007; Ouimet, et al, 2015; Tefft et al, 2012). Presumably, teenage passengers increase crash risk through social influence, either pressure to increase risk or social norms that favor more risky driving (Ouimet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Driving with a teenage passenger is considered to be a factor uniquely associated with teen crash risk (Williams et al, 2007; Ouimet, et al, 2015; Tefft et al, 2012). Presumably, teenage passengers increase crash risk through social influence, either pressure to increase risk or social norms that favor more risky driving (Ouimet et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Driving with a teenage passenger is considered to be a factor uniquely associated with teen crash risk (Williams et al, 2007; Ouimet, et al, 2015; Tefft et al, 2012). Presumably, teenage passengers increase crash risk through social influence, either pressure to increase risk or social norms that favor more risky driving (Ouimet et al, 2015). In their review of driving restrictions at the provisional license stage, Lin and Fearn (2003) suggested that driving with a teen passenger significantly increased the likelihood of involvement in fatal crashes, and that the risk increased with the number of teenage passengers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the presence of an adult passenger, age 35 years or older, was associated with decreased teen drivers' risk of involvement in any police reported crash, as well as involvement in fatal crashes (46% and 62%, respectively). In a recent systematic review on the influence of passengers on young drivers, Ouimet et al (2015) concluded that passenger presence increased the overall fatal crash risk of teens compared to solo driving, but the relationship between teenage passenger presence and non-fatal crash outcomes could not be confirmed. An observational study on teens' risky driving found that teen drivers were more prone to engage in risky driving behavior in the presence of teenage passengers (Simons-Morton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the current study, a suburban driving setting, using a phone while stopped at traffic lights, and driving with passengers were identified as common scenarios. While a recent meta-analysis of 17 studies found there was a greater crash risk (fatal and non-fatal) for young drivers carrying passengers compared to when driving alone (Ouimet et al, 2015), other studies have found that interacting with a mobile phone was less likely when a passenger was present (e.g., Rosenbloom & Perlman, 2016). In order to explore these findings further, two messages were developed with passengers present.…”
Section: Message Focusmentioning
confidence: 99%